Recipes for Revision: Digesting American Empire in the Philippines via Filipina Literature in Spanish - Lifshey, Adam (Archīum Ateneo, 2024)
This essay investigates the intersections of American empire and American feminism via literature by Filipinas in Spanish. Texts written in Manila by hispanophone Filipinas who were also American subjects and American nationals present a defamiliarizing phenomenon that casts anew standard historical-literary accounts of the 20th century United States. The literary output of Maria Paz Zamora, for instance, reveals an America that emerges on shores not commonly taken to be American at all and yet are more indicative, arguably, of the modern United States than any other. Paz Zamora was the first Asian woman to produce a short story collection in Spanish (Mi obolo, 1924), the co-author of a bilingual cookbook (Everyday Cookery for the Home, 1930 and 1934), and the only Filipina known to have published a World War II memoir in Spanish. Like all Filipinos during the American colonization of the archipelago, however, Paz Zamora was also an American subject designated by the United States as an American national. This essay analyzes her oeuvre within the contexts of early Filipina literature in general and within the gender politics of the Spanish-language press in Manila of her day, but argues ultimately that a principal reason for studying her is to seek a globalized revision of what has been, ever since 1898, a globalized America.